Establishing effective learning activities to facilitate undergraduate professional interaction course / Rajani Chandra Mohan ... [et al.] - Chandra Mohan, Rajani; Abu Samah, Siti Akmar; Christ Dass, Laura; Subramaniam, Geetha (Akademi Pengajian Bahasa, 2019)
English for Professional Interaction is a course that was designed to prepare final year undergraduates for communicative demands in the workplace. As communication is an essential element in professional socialization, undergraduates preparing to complete their tertiary education are required to do this course to develop their interpersonal skills through communicative language activities modelled on situations in the workplace. However, novice language teachers who lack workplace-based inter-professional practice, face challenges not only in developing teaching content, but also in aligning teaching materials with workplace contexts. This paper explores the utility of developing a variety of methods and materials drawn primarily from sources for improving core interpersonal skills alongside communicative proficiency to help novice ESL teachers/facilitators. Novice ESL teachers refer to teachers in service with less than 5 years of teaching experience. Taking a conceptual approach, it provides insights for content development and illuminates the importance of bridging the gap between university-based inter-professional education and work place-based inter-professional practical experience for L2 novice teachers. Obliquely, it helps L2 undergraduates develop real value for language and proper outlook on communication.